INCREASING VOCABULARY MASTERY THROUGH INCIDENTAL AND CONTRIVED LEARNING FOR THE FIRST YEAR STUDENT OF MACHINE ENGINEERING OF SMK NEGERI 2 KLATEN - DEWI, ANITA SARI (2011)
This research aims to increase vocabulary mastery through incidental and contrived learning for the first year student of machine engineering of SMK Negeri 2 Klaten. The objectives of this research is to describe the implementation of incidental and contrived learning to increase the student's vocabulary mastery at the first year of Engineering of SMK Negeri 2 Klaten and describe the advantages and disadvantages of teaching vocabulary by using incidental and contrived learning. This research is classroom action research. The analysis is qualitative method where the data are taken from documentation, interview, test, and observation analysis. The object of the study is the implementation of incidental and contrived learning to increase the student's vocabulary mastery to the first year students of Mechanical Engineering of SMK Negeri 2 Klaten. The result of the research shows that incidental and contrived learning can increase the students' vocabulary mastery. Before the observation, the teacher's teaching technique was monotonous and the students easily get bored. The students tended to speak with other friends than listen to what the teacher said, so the material cannot be learned well, so the result of vocabulary mastery us poor. After the observation using incidental and contrived learning, the vocabulary mastery of the first year students of Mechanical Engineering of SMK 2 Klaten increases. The advantages of using Incidental and Contrived learning on teaching vocabulary are: The material are flexible, depending on the atmosphere or the situation within the class, the student will not get bored if the teacher able to use the method correctly, the students will have an extra new vocabulary from the new material of incidental learning, the teacher can create their own technique with the incidental learning. The disadvantages of using Incidental and Contrived learning on teaching vocabulary are: the students were confused when sometimes teacher changed the material that is not based on the curriculum, the teacher needed more material from the both incidental and contrived learning.